Motor-cognitive interaction in adults with spina bifida: dual-task effects. - Bendt, Martina; Butler Forslund, Emelie; Hagman, Göran; Ekman, Urban; Bezuidenhout, Lucian; Johansson, Hanna; Rydström, Anders; Hultling, Claes; Seiger, Åke; Franzén, Erika (Spinal Cord, 2025)
Study design: Cross-sectional design. Objectives: To study motor-cognitive interaction during walking while performing a cognitive task (dual-task [DT]) in ambulatory adults with spina bifida (SB). Setting: A specialized spinal cord center, The Spinalis clinic at Aleris Rehab Station Stockholm, Sweden. Methods: Assessments of muscle strength and ambulatory function were performed. Gait was assessed with a sensor-based system with/without the auditory Stroop. Timed-up-and-go (TUG) with/without a cognitive task was also assessed. Regarding cognitive function, episodic memory, executive function, and processing speed were assessed. The percentage of difference between single-task (ST) and dual-task (DT) was used to calculate the DT effect (DTE) as cost or benefit. Differences were analyzed with t-test and Wilcoxon's signed rank test. Results: Forty-one persons were included, mean age 37 years (SD 12) and 20 (49%) were women. Thirty-four completed the DTE analysis. Seven could not perform the cognitive task and/or gait data and could not be registered. There was a DT cost on gait speed (4%), stride length (3%) and double support phase (3%), and cognitive function showed a cost of 3%. DTE for TUG was a 26% cost. Conclusion: We showed a DT cost on gait, possibly indicating fall risk during DT walking. The largest DT cost was seen during TUG with a cognitive task, indicating a valuable clinical test for motor-cognitive performance for adults with SB. This study is pioneering in that it increases our understanding of DT performance in ambulatory adults with SB which could facilitate development of targeted rehabilitation interventions and self-management strategies.